Service Quality of Teaching Vocational Education And Training (TVET) And Students Performance In The Federal Polytechnic Ilaro, Nigeria - Makinde, Wasiu; Bamiro, Tolulope Oluwatosin (International Journal of Entrepreneurship and Business Management, 2022)
Technical, Vocational, Education and Training (TVET) has been identified as an effective strategy for improving socio-economic development of both developing and developed nations. This study aims at assessing the student’s experience of service quality of TVET in the Federal Polytechnic Ilaro, Nigeria. The study reviewed concept of service quality and TVET, reviewed of previous findings from related studies and adopted SERVQUAL model as framework for the study. The population of the study comprised of about 10,250 student during 2021/2022 academic session in the Federal Polytechnic Ilaro, Nigeria. The study adopted Krejcie and Morgan sampling technique to have 375 sample size. Primary and secondary sources of data collection were adopted for the study. Data collected were analysed through descriptive and inferential statistics of frequency distribution table, percentage, mean value and linear regression analysis. The study discovered that physical facilities, comfortable classroom, adequate academic resources and appearance of physical facilities are highly ranked tangibility of TVET. Lecturer’s good knowledge, lecturer’s politeness and security measures are highly ranked in assurance of TVET and support staff fairness, lecturers sincere interest on student and lecturer’s teaching capability are highly ranked reliability of TVET. Also, lecturer’s adequate capacity, treatment of complaints by student and support staff availability are highly ranked responsiveness of TVET and, polytechnic fair treatment, support staff attention to students and lecturer’s support to individual students are highly ranked empathy of TVET in the Federal Polytechnic, Ilaro, Ogun State Nigeria. Therefore, the study concluded that students are experiencing service quality of TVET in the Federal Polytechnic, Ilaro Ogun State Nigeria.